ANTIPHOSPHOLIPID SYNDROME AND SYSTEMIC LUPUS ERYTHEMATOSUS: WHAT DISEASE IS A CAUSE OF ORGAN DAMAGES? - F. A. Cheldieva; T. M. Reshetnyak; S. G. Radenska-Lopovok; Yu. O. Korsakova; A. M. Lila (Научно-практическая ревматология, 2020)
The paper describes a clinical case of a male patient with verified systemic lupus erythematosus (SLE) and manifestations of lupus nephritis with impaired renal nitrogen excretory and filtering functions, central nervous system lesion (focal epilepsy), hematological (hemolytic anemia) and immunological (anti-double-stranded DNA antibodies, hypocomplementemia, positive antinuclear factor) disorders, and antiphospholipid syndrome (APS). The disease originated from APS: thrombosis in the radial and ulnar arteries. Subsequently, organ damages were considered as a consequence of thrombotic microangiopathy, which can occur with both APS and SLE.